2017
DOI: 10.2174/1874364101711010355
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Risk Factors and Treatment of Dry Eye Disease in Type 1 Diabetes Before Corneal Complications at Sindh Institute of Ophthalmology And Visual Sciences

Abstract: Objective:The objective of this study was to assess and determine the risk factors and treatment of dry eye disease in type 1 diabetes before any ocular surface or corneal complication occurs. This study was conducted at Sindh Institute of Ophthalmology And Visual Sciences, Hyderabad, Pakistan.Methodology:Subjects and methods for observational study were undertaken at the Department of Ophthalmology Sindh Institute Of Ophthalmology And Visual Sciences, Hyderabad, Pakistan. Hundred confirmed cases of type 1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…Participants with T1DM had a reduced tear volume compared to controls in the SIT. These results are consistent with other research in adults with T1DM [ 43 , 44 ], children and adolescents [ 42 , 45 ], and subjects with T2DM [ 33 , 46 49 ] but disagree with Ferdousi et al [ 50 ]. Shujaat et al [ 45 ] suggested that diabetes may cause damage to the microvasculature and innervation of the main lacrimal gland, affecting tearing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants with T1DM had a reduced tear volume compared to controls in the SIT. These results are consistent with other research in adults with T1DM [ 43 , 44 ], children and adolescents [ 42 , 45 ], and subjects with T2DM [ 33 , 46 49 ] but disagree with Ferdousi et al [ 50 ]. Shujaat et al [ 45 ] suggested that diabetes may cause damage to the microvasculature and innervation of the main lacrimal gland, affecting tearing.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding TFBUT, patients with T1DM had lower TFBUT values than controls, corroborating the results of other authors [45,50] and supporting the results obtained in the NIBUT, although there are also some authors who disagree with this result.…”
Section: Invasive Tear Film Testssupporting
confidence: 90%
“…An intriguing finding is that longer DM duration appeared to be a protective factor for the development of DED in our study. In previous studies, DM duration either did not have a significant effect or is a contributing factor for DED (32,33). However, studies had discovered that, in patients with longer DM duration, self-reported symptoms and decreased corneal sensitivity along with inferior whorl length destruction were noted with high underdiagnosis rate for DED (8,34).…”
Section: Discussionmentioning
confidence: 95%
“…We further identified patients with DED using ICD-9-CM 370. 33 (x = 1, 2, 3, 9), H04.12x (x = 1, 2, 3, 9), and for diagnostic accuracy, we excluded those who did not receive either lubricant and/or topical anti-inflammation agent after the diagnosis was established. Those with DED were classified as the DED group, and those without DED were classified as the non-DED group.…”
Section: Ded and Non-ded Groupsmentioning
confidence: 99%
“…58 One could speculate that in diabetes, where there is an increase in dry eye, cellular desquamation is escalated. [59][60][61][62][63][64][65][66] In a diabetic rat model, terminal deoxynucleotidyl transferase dUTP nick end (TUNEL) labeling was used to measure the number of apoptotic cells in the corneal epithelium. 67 Importantly, the authors found a five-fold increase in apoptotic cells compared to the non-diabetic control.…”
Section: Apoptosis and Surface Epithelial Cell Desquamationmentioning
confidence: 99%